UNIQUE CUSTOMS AT ENGLISH WEDDINGS - Mokhinur Sotvoldieva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this scientific work, the similarities and differences of the national-cultural traditions of the Uzbek-English wedding ceremonies related to marriage will be discussed.